2011
DOI: 10.4028/www.scientific.net/amr.391-392.688
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Thermal Behavior of Recycled PET Modified by PMDA

Abstract: In this work pyromellitic dianhydride (PMDA) was used as the chain extender to increase the molecular weight of the recycled poly(ethylene terephthalate) (R-PET) and improve the rheological properties of the R-PET. The reaction was performed in a Brabender torque rheometer. The rheological and thermal characterization were performed by means of a fusion index instrument and a differential scanning calorimeter (DSC ) to compare the effectiveness of the chain extending reaction of different percentages of PMDA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…45 Wang et al confirmed that the PMDA content increases above 1.0 wt%, intensifying degradation leads to a decrease in molecular weight and an increase in MFI. 4 Therefore, the PMDA content was set between 0.25 and 1.0 wt%. In Figure 6, the torque value of the modified rP-PET improved as compared with that of rP, and this could be attributed to the formation of chain entanglement increasing the weight average molecular weight (M w ) and molecular weight distribution (MWD).…”
Section: Reactive Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…45 Wang et al confirmed that the PMDA content increases above 1.0 wt%, intensifying degradation leads to a decrease in molecular weight and an increase in MFI. 4 Therefore, the PMDA content was set between 0.25 and 1.0 wt%. In Figure 6, the torque value of the modified rP-PET improved as compared with that of rP, and this could be attributed to the formation of chain entanglement increasing the weight average molecular weight (M w ) and molecular weight distribution (MWD).…”
Section: Reactive Processingmentioning
confidence: 99%
“…28 In several studies, it has been reported that the melt viscosity and rheological properties of PET modified by ADR have been improved. 4,8,22,47 Two-step reaction for chain extension between PET and PMDA was required, and in the first step, a ring-opening reaction between the hydroxyl group of PET and the anhydride functional groups of PMDA formed two carboxyl groups. 47 At the second step, the hydroxyl group of PET additionally reacted with PMDA.…”
Section: Reactive Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…More studies on the rheological behavior showed that adding PMDA increased the rPET molecular chain length and branching through the chemical reactions with the end groups of rPET. The melt flow index and melt strength of the rPET mixed with PMDA were investigated by Wang et al 23 and a decrease in the melt flow index and an increase in the melt strength were noted as the weight percent of PMDA increased from 0.25 to 1.25 wt%. Hirach et al 22 also noted an increase in the viscosity and molecular weight when different weight fractions of PMDA ranging from 0.1 to 0.3 wt% were added to PET.…”
Section: Introductionmentioning
confidence: 99%